Financial Aspects of Desa Pelangi Sentul Private Commercial Hunting - Ainy Amelya Utami; Yanto Santosa; Arzyana Sunkar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Hunting tourism is a form of sustainable use of wildlife that can be done through commercial hunting, thus commercial hunting can contribute to the national economy. Indonesia has 11 public hunting areas but none are well-operated. Beside public hunting area, Indonesia also has private hunting areas. One such place is Desa Pelangi Sentul Private Hunting Area, located in Babakan Madang Sub-Districts of Bogor District, West Java. The objective of this study was to examine the financial benefits of private hunting area in Desa Pelangi Sentul Private Hunting Area through the calculation of Net Present Value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR). The financial analysis showed that Desa Pelangi Sentul Private Hunting Area exertion gained NPV Rp 13 413 719 092 , BCR 1.563, and IRR 18% .This means the exertion is acceptable. Sensitivity analysis also showed that De’Pes Private hunting Area exertion could be held until the benefit decreased 10% with the investation cost fixed, and the investatioin cost increased until 180% with the fixed benefit.